2019
DOI: 10.1016/j.schres.2018.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cariprazine on negative symptoms in patients with acute schizophrenia: A post hoc analysis of pooled data

Abstract: Although currently approved antipsychotics exert efficacy on positive symptoms of schizophrenia, treatments for negative symptoms remain a major unmet need. Post hoc analyses were used to investigate the possible efficacy of cariprazine in patients with moderate/severe negative symptoms of schizophrenia and no predominance of positive symptoms. Data were pooled from 2 randomized, double-blind, placebo- and active-controlled cariprazine studies in patients with acute schizophrenia (NCT00694707, NCT01104766). An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 34 publications
4
42
0
3
Order By: Relevance
“…Furthermore, the superiority of cariprazine over placebo and aripiprazole in improving PANSS-factor score for negative symptoms (PANSS-FSNS) emerged in post-hoc analyses of data pooled from two randomized, double-blind, placebo-and activecontrolled studies in patients with acute schizophrenia with moderate/severe negative symptoms and no predominance of positive symptoms. The benefit of cariprazine on negative symptoms was at least partially independent from improvements in positive symptoms and EPS (Earley et al, 2018b). A meta-analysis confirmed this specific domain of efficacy (Corponi et al, 2017) and it also suggested that young patients with a relatively short history of disease may benefit the most from cariprazine.…”
Section: Schizophreniamentioning
confidence: 75%
“…Furthermore, the superiority of cariprazine over placebo and aripiprazole in improving PANSS-factor score for negative symptoms (PANSS-FSNS) emerged in post-hoc analyses of data pooled from two randomized, double-blind, placebo-and activecontrolled studies in patients with acute schizophrenia with moderate/severe negative symptoms and no predominance of positive symptoms. The benefit of cariprazine on negative symptoms was at least partially independent from improvements in positive symptoms and EPS (Earley et al, 2018b). A meta-analysis confirmed this specific domain of efficacy (Corponi et al, 2017) and it also suggested that young patients with a relatively short history of disease may benefit the most from cariprazine.…”
Section: Schizophreniamentioning
confidence: 75%
“…Due to the specific pharmacodynamics profile, (partial agonist of the dopamine receptors D2/D3, with a tenfold affinity for the D3 receptor with partial agonism for the serotonin [5-hydroxytryptamine] 5HT1A receptor, as well as antagonism at 5HT2B and 5HT2A receptors and for the histamine H1 receptor), the panel members judge cariprazine to be a drug with important clinical and pharmacological advantages over other antipsychotic agents [ 17 , 19 21 ]. The main advantage is assumed in its superior efficacy in treating the negative symptoms of schizophrenia—representing a major step forward for patients, carers and healthcare professionals alike [ 22 , 23 ]. The panel noted the evidence on the ability of cariprazine to reduce troublesome side-effects that frequently cause patients to discontinue some of the other antipsychotics, including anti-cholinergic (dry mouth, constipation, urinary retention, exacerbation of the dangerous effects of closed-angle glaucoma), anti-adrenergic (orthostatic hypotension), antihistaminergic (sedation, weight gain) and metabolic (weight gain, increased cholesterol, increased triglycerides) as well as a reduced risk of arrhythmias [ 24 , 25 ].…”
Section: Results: Data Gathering and Recommendationsmentioning
confidence: 99%
“…10,12 PANSS has been used in various studies to evaluate treatment effects on symptoms including moderate/severe negative symptoms of schizophrenia. 13,14 Furthermore, the negative subscale of the PANSS was found to have adequate psychometric properties and that each of the subscales of the PANSS formed independent constructs. 6,15 Appropriate management of negative symptoms is a critical unmet need, primarily because the functional impairment due to negative symptoms cannot be appropriately addressed by treating positive symptoms alone.…”
Section: Introductionmentioning
confidence: 96%